Pengaruh Tren Makanan Kekinian terhadap Pola Konsumsi dan Peluang Inovasi Pangan Sehat di Gorontalo - Niluh Arwati; Desi Novitasari; Jamaludin Abdi Purwanto (Lembaga Yasin AlSys, 2026)
Although contemporary food and beverage trends have received attention in food studies and consumer behavior research, studies that specifically examine their influence on community consumption patterns and opportunities for healthy food innovation in Gorontalo remain limited. This study aims to explore the influence of contemporary food trends on community consumption patterns and identify opportunities for developing healthy food products in Gorontalo. This study used a descriptive qualitative approach involving consumers and micro, small, and medium enterprises (MSMEs) in the food and beverage sector. Data were collected through observation, interviews, and questionnaires administered to consumers and MSME actors. The results showed that contemporary food and beverage products, such as coffee, boba, fast food, and various modern snacks, remain the main choices of the community, particularly students and young people. Consumption preferences were influenced by practicality, taste, price, attractive packaging, and the influence of social media. However, increasing public health awareness has also encouraged interest in low-sugar products, fruit-based beverages, and healthier traditional foods. This study also found opportunities for healthy food innovation through the development of Gorontalo traditional foods with a more modern concept without eliminating their nutritional value and local identity. The conclusion of this study emphasizes the importance of balancing market trends and health aspects in food product development. The implications of this study contribute to understanding changes in community consumption patterns and provide practical input for MSME actors in developing healthy food products, improving product quality, and utilizing digital media to reach consumers who are increasingly health-conscious.